Program Pemberdayaan Masyarakat Terkait Pengolahan Limbah Kotoran Ternak dengan Aerob-Fermentation Methods - Parwoto, Parwoto; Priyatono, Margo; Jatmiko, Bambang (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2018)
The purpose of this devotion program is to provide strengthening understanding and technical capability to the community of Klampis hamlet, related to the processing of cattle manure waste (kohe) which is still organic fertilizer by using aerob-fermentation methods. Method of implementation of devotion is survey and observation, counseling urgency of waste treatment, technical training of organic fertilizer processing, technical accompaniment in process-ing group of organic fertilizer. Results and discussion of this devotion program as follows: 1) the potential of livestock manure is compiled Klampis if processed into organic fertilizer is more than enough to meet the needs of agricultural land fertilizer, 2) the process of public awareness is done by counseling about the urgency of cattle dung sewage treatment with lecture method and discussions; 3) technical training methods undertaken using tutorial methods and practices related to the manufacture of stale MOL and organic fertilizer manufacture with aerob-fermentation methods using MOL and Rumen; 4) technical accompaniment performed intensively and gradually towards the organic fertilizer maker group from start preparation of materials, mixing, stirring, incubation, and reversal. The outcomes of this empowerment program are self-sufficient journals (Journal of Rural and Urban Development) Keywords: Community, empowerment,         aerob-fermentation methods